2010
DOI: 10.1007/s10856-010-4187-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behaviour and surface characterisation of Zr exposed to an SBF solution containing glycine, in view of dental implant applications

Abstract: Zr and Ti alloys are extensively used in the biomedical field owing to their optimal mechanical properties and excellent corrosion resistance. Fully ceramic implants based on zirconia are appealing with respect to the traditional Ti-based metallic ones for several reasons, such as: (i) improved aesthetic impact, (ii) better biocompatibility and (iii) better osteointegration. Nevertheless, fully ceramic implants exhibit serious mechanical and clinical drawbacks, chiefly brittleness and impossibility of post-imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It incorporates two time constants which can be deducted from Bode plots. In both the cases, there is a decrease of α O which means deviation from pure capacitance due to surface inhomogenity [35]. It may be a result of apatite deposition on the surface of nanotubes.…”
Section: Eis Measurementsmentioning
confidence: 93%
See 2 more Smart Citations
“…It incorporates two time constants which can be deducted from Bode plots. In both the cases, there is a decrease of α O which means deviation from pure capacitance due to surface inhomogenity [35]. It may be a result of apatite deposition on the surface of nanotubes.…”
Section: Eis Measurementsmentioning
confidence: 93%
“…9a-d. For the interpretation of the experimental data, we used equivalent circuits available in the literature [12,[35][36][37], which have been often applied to dense and porous oxide layer formed on the metal surface immersed in the electrolyte. Both models are based on Randles circuit and are shown in Fig.…”
Section: Eis Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 It was suggested that their corrosion resistance would be further improved by alloying 16,17 or surface treatment. 18,19 The oxinium (surface oxidized Zr-2.5Nb alloy) has been commercially used as knee and hip femoral heads in total joint arthroplasty owing to its superior wear resistance. 20,21 Moreover, the surface oxidized zirconium alloy exhibited an excellent anti-bacterial property.…”
Section: Introductionmentioning
confidence: 99%
“…Both species were demonstrated to adsorb onto the metal surface but contradictory effects (suppressing or accelerating) were claimed on the corrosion of Zr. 26,27 It has also been reported that the presence of H 2 O 2 reduces the corrosion resistance of thermally oxidized Zr5Ti where surface oxides are mostly composed of ZrO 2 . 29 No studies have been reported on the combined effect of H 2 O 2 and albumin in terms of corrosion and corrosion products.…”
mentioning
confidence: 97%